Role of Roguing in Healthy Seed Potato Production - Sadawarti, Murlidhar J.; Singh, S. P.; Katare, Subhash; Samadhiya, R. K.; Singh, Y. P.; Sharma, S. K.; Singh, Surender; Gupta, Shyam Kumar; Devi, Sugni; Buckseth, Tanuja; Kumar, Vinod; Singh, Brajesh; et al. (Chronicle of Bioresource Management, 2023)
Producing high quality seed is utmost important for higher productivity and best returns to the potato growers. Seed plot technique is the well developed technology for seed potato production in India. Roguing is one of the most important practices for producing high quality seed in potato. Virus-vector relationship is to be taken into consideration which affects the rouging process and quality of the seed potato. It provides an effective means to break infection cycle. Proper identification of rouge, following the step by step process and taking prequationary measures is very much important for high quality seed production which will pass through certification process.